Effects of Mushroom and Chicory Extracts on the Physiology and Shape of Prevotella intermedia, a Periodontopathogenic Bacterium. (11th September 2011) - Signoretto, Caterina; Marchi, Anna; Bertoncelli, Anna; Burlacchini, Gloria; Tessarolo, Francesco; Caola, Iole; Pezzati, Elisabetta; Zaura, Egija; Papetti, Adele; Lingström, Peter; Pratten, Jonathan; Spratt, David A.; et al.
Abstract : Contrary to the common assumption that food has a negative impact on oral health, research has shown that several foods contain a number of components with antibacterial and antiplaque activity. These natural compounds may be useful for improving daily oral hygiene. In this study we evaluate the mode of antimicrobial action of fractions of mushroom and red chicory extracts on Prevotella intermedia, a periodontopathogenic bacterium. The minimal inhibitory concentration corresponded to 0.5x compared to the natural food concentration for both extracts. This concentration resulted in a bacteriostatic effect in mushroom extract and in a slightly bactericidal effect in chicory extract. Cell mass continued to increase even after division stopped. As regards macromolecular synthesis, DNA was almost totally inhibited upon addition of either mushroom or chicory extract, and RNA to a lesser extent, while protein synthesis continued. Cell elongation occurred after septum inhibition as documented by scanning electron microscopy and cell measurement. The morphogenetic effects are reminiscent of the mode of action of antibiotics such as quinolones or β -lactams. The discovery of an antibiotic-like mode of action suggests that these extracts can be advantageously employed for daily oral hygiene in formulations of cosmetic products such as mouthwashes and toothpastes.